Profile of Women Suffering Postpartum Hemorrhage: Recent Update In Salatiga Region General Hospital, Central Java, Indonesia - Tauho, Kristiani Desimina; Tampubolon, Rifatolistia; Mone, Dori Maria (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Postpartum hemorrhage is a significant problem related to maternal death. The cause of the second highest maternal mortality rate in Central Java is bleeding, which is as much as 21.23%. Objective: This study aimed to identify the current profile of mothers who experienced postpartum hemorrhage at the Salatiga City Regional General Hospital. Method: This study uses a quantitative method with a retrospective approach. The data collection technique used document tracing in the form of medical records with a checklist sheet instrument. This study concluded 89 medical records of women diagnosed with postpartum hemorrhage from 2017 to 2021. Result: The characteristics of women who experienced postpartum hemorrhage were mostly productive age, secondary education, mothers who worked as housewives, Javanese ethnicity, married, parity 2-4, single pregnancy, 2 to 4 years inter-pregnancy interval, and retained placenta. Almost all of these features are not risk factors for postpartum hemorrhage. Conclusion: Based on the study’s results, postpartum hemorrhage can happen in any woman who are having or not having risk factors of postpartum hemorrhage. Recommendation: Precautions need to be taken for all birthing mothers regardless of their risk factor status.